Community-Driven Waste Management: The Waste Bank Initiative in Taman Banten Lestari Housing Estate, Serang City - Nurikah Nurikah; Eki Furqon (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
Garbage Banks are one of the innovations that societies make in reducing waste at their source: environment-based waste management and garbage management starting at the source. Garbage can can be a environmental problem, especially garbage from communities in which garbage comes from communities in which it is not treated well, so it will become a load of garbage-based garbage Banks, which are based on citizen citizen participation become an alternative to garbage solutions based on principles of distribution, reuse, Recyle and replant (4r) mean communities become social capital to phase out the existence of trash Banks in household garbage management programs. A change in people's thinking on the management of household garbage should be built through the education of junk management based on community participation to reduce garbage from its source so that people should be aware of and eventually integrated into community-based garbage bank programs. The method of community participation in the home environment should be part of a region that should be done through both educational and dialogue and referrals as an adaptation of the Banks of garbage to the community to act out environmental concerns through the participation of trash based programs through trash Banks. Public-based waste bank education programs will impact the next ward in which people will be involved in high rates of engagement to move together to maintain the environment, especially the city.